Morphological, Physiological and Nutritional Studies on Rhizoctonia solani and Their Effect on Seed Germination in Rice - Husain, Raja; Khan, N. A.; Shivani; Gyanendra, Kunvar; Vikram, Nitin; Singh, Ashu; Yadav, Garima; Bharti, Pradeep Kumar; Dwivedi, D. K.; Singh, K. N. (International Journal of Bio-resource and Stress Management, 2016)
The sample showing disease (sheath blight) symptoms in rice were collected from six states Gujarat, Karnataka, Pantnagar, Uttar Pradesh, Haryana and Punjab. The isolates (Gujarat, Karnataka, Pantnagar, Uttar Pradesh, Haryana and Punjab) of R. solani, were isolated on PDA plates were incubated for 5 days at 28±1 °C. Colony colour, growth pattern, and diameter growth showed great diversity in all the isolates. Based on the colony pigmentation, all the isolates were assigned into 4 groups: dark brown, dirty white, milky white and Yellowish brown. Isolates were grown on five different media; PDA was found the best media for growth and development in comparison to others. The maximum growth was found in two isolates, Gujarat and Karnataka (90 mm or 89.07) after 72 hrs. The maximum number of sclerotia was recorded in Gujarat isolate (125.33) followed by Karnataka (75.67) on Czapek’s dox agar while the minimum number of sclerotia was observed in Pant Nagar (6.33) on yeast extract agar medium. The maximum weight of sclerotia was recorded in Gujarat isolate (194.02 mg) followed by Karnataka (186.79 mg) on PDA medium. The fourteen days old broth culture of oat meal broth of different isolate of R. solani significantly reduced the radical length and plumule length of the germinated seeds of Pusa Basmati-1 and Tetep as compared to check. Tetep showed the less reduction in germination per cent than Pusa Basmati-1, known as moderately resistant cultivar. The effect of Gujarat isolates was found the highly pathogenic than other isolates on seed germination of both the cultivar.